Legal Standing in Environmental Litigation before Regional International Courts in Africa and Latin America - Kahl, Sonja (The Opole Studies in Administration and Law, 2023)
This article compares the rules governing legal standing before selected regional international judicial and quasi-judicial bodies in Africa and Latin America from a perspective of environmental litigation. The focus is on active legal standing of private entities in contentious proceedings against states. The article sytematizes the rules governing legal standing into two broad categories: rights based and public interest litigation. Subsequently, the approach of each court will be analyzed on the basis of its procedural rules and jurisprudence. Several trends can be identified, including a tendency of human rights courts to move towards public interest litigation, a trend to grant non-governmental organizations a privileged position to initiate environmental litigation, and the development of Community rights based approached by courts for regional economic integration that could become relevant in the future.